Response to the Letter to Editor Regarding "Stevia Rebaudiana Bertoni, Source of a High Potency Natural Sweetener: A Comprehensive Review on the Biochemical, Nutritional and Functional Aspects Extraction and Safety of Stevioside" - Lemus-Mondaca, R (2012)
Sin Editorial Disponible